Relatório de Estágio Profissional "Estágio Profissional - a caminhada motivadora: -Entre a frustação e o esforço da superação" - Daniela da Costa Pereira (2019)
This document emerges as the last stage of the Professional Internship and it assumes a dual function: a first-person account of the entire professional internship process, as a learning tool for the author, future teacher of Physical Education. This reports all the personal experience in which will be highlighted the main difficulties and frustrations felt, as well as the successes achieved during the process of professional internship of Physical Education, held at the D.Dinis School Group in Santo Tirso. This report report is divided into four parts / themes: in the first part will be presented the aspects of the document, the second part will be devoted to the biographical framework, the various expectations / conceptions about the professional internship and the student's performance. This is a highly preponderant element of the whole experience. The third part of the document is related to all practical experiences lived in the performance context, namely everything related to the conduction of the teaching-learning process (conception, planning, realization and evaluation), as well as all the activities that were developed. throughout the year outside the teaching component and which contributed to the training as a teacher. Finally, some final considerations will be made about the lived experiences, positive and less positive points, which helped in the formation and development of self identity as a teacher.